2020
DOI: 10.2196/17648
|View full text |Cite
|
Sign up to set email alerts
|

Toward Optimal Heparin Dosing by Comparing Multiple Machine Learning Methods: Retrospective Study

Abstract: Background Heparin is one of the most commonly used medications in intensive care units. In clinical practice, the use of a weight-based heparin dosing nomogram is standard practice for the treatment of thrombosis. Recently, machine learning techniques have dramatically improved the ability of computers to provide clinical decision support and have allowed for the possibility of computer generated, algorithm-based heparin dosing recommendations. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 21 publications
(25 reference statements)
0
60
0
Order By: Relevance
“…As validated in a previous study [ 11 ], a shallow neural network model works best from among several machine learning models for the heparin outcome prediction task. In this study, we used a fully connected shallow neural network model [ 16 , 17 ] to predict the therapeutic effect (subtherapeutic, normal therapeutic, or supratherapeutic) of patients after 8 hours of heparin treatment.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…As validated in a previous study [ 11 ], a shallow neural network model works best from among several machine learning models for the heparin outcome prediction task. In this study, we used a fully connected shallow neural network model [ 16 , 17 ] to predict the therapeutic effect (subtherapeutic, normal therapeutic, or supratherapeutic) of patients after 8 hours of heparin treatment.…”
Section: Methodsmentioning
confidence: 90%
“…The results show that the machine learning–based model can effectively predict the aPTT response after the initial dosing and in a step-by-step pattern, which can contribute to decreasing the duration of the therapeutic regime and avoiding treatment-related risks. In our previous work, we demonstrated that the shallow neural network algorithm performed best compared to algorithms such as extreme gradient boosting, adaptive boosting, and support vector machine [ 11 ]. Based on our local clinical database and modified treatment pattern, we validated our previously developed model and demonstrated the applicability of this machine learning–based algorithm for UFH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are shown in Table 1. Five studies 27,28,30,32,33 described ML models aimed at achieving a therapeutic aPTT in the intensive care unit (ICU) setting. Three studies 29,31,34 conference proceedings [28][29][30][31][32] and three in peer reviewed journals.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Therefore, to avoid the occurrence of adverse reactions, it is necessary to monitor the concentration of ionized calcium in the body, and timely adjust the calcium supplementation rate [17]. In recent years, with the rapid development of machine learning technologies, data-driven methods has been introduced in this fields to provide algorithm generated outcome predictions and dosing related clinical decision supports for clinicians [18,19]. These previous studies demonstrated that by closely monitoring the bedside patient data, it is possible to predict treatment outcomes, and to provide computer generated recommendations.…”
Section: Introductionmentioning
confidence: 99%